Mechanical performance of modified cement paste made with micro-fine POFA in ammonium nitrate environment. (20th February 2018) - Tasnim, Sadia; Rahman, Muhammad Ekhlasur; Ahmadi, Raudhah Binti
Highlights: Modified cement paste have been made using micro-fine palm oil fuel ash (POFA) in this study. Compressive strength, Energy Dispersive X-ray (EDX) and a Scanning Electron Microscopy (SEM) test were carried out. It was observed that, samples replaced with 20% POFA had the best results. Abstract: An experimental study was conducted on modified cement paste cubes in ammonium nitrate solution. The modified cement paste was made using micro-fine palm oil fuel ash (POFA) as partial cement replacement. Compressive strength, Energy Dispersive X-ray (EDX) and a Scanning Electron Microscopy (SEM) test were carried out. The 50 mm cubes were cast containing 0%, 10%, 20% and 30% of POFA as cement replacement using constant water to cement ratio of 0.4. After 28 days of water curing, 50% of samples were immersed in 20% ammonium nitrate solution and the rest of samples were kept in room temperature. It was observed that, samples replaced with 20% POFA had the highest compressive strength in ammonium nitrate solution. In addition to that, it was also observed through EDX and SEM analysis that cement replaced with 20% POFA had lower Ca/Si ratio and there were more C-S-H structures in the modified cement paste in ammonium nitrate solution. Lower Ca/Si ratio and more C-S-H structures is an indication of higher pozzolanic reactions in the paste.